2018
DOI: 10.1093/nar/gky790
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae chromosome 2 copy number is controlled by the methylation-independent binding of its monomeric initiator to the chromosome 1 crtS site

Abstract: Bacteria contain a primary chromosome and, frequently, either essential secondary chromosomes or dispensable megaplasmids of plasmid origin. Incoming plasmids are often poorly adapted to their hosts and their stabilization requires integration with the host's cellular mechanisms in a process termed domestication. All Vibrio, including pathogenic species, carry a domesticated secondary chromosome (Chr2) where replication is coordinated with that of the primary chromosome (Chr1). Chr2 replication is triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…If the crtS site is replicated after ori2 has been copied by replication forks coming from ori1 as in the case of NSCV2, there is no need to initiate at ori2 because the copy number of crtS and ori2 are in balance already. The lack of initiation at ori2 in NSCV2 is therefore fully consistant with and confirmatory to the findings of the aforementioned studies ( de Lemos Martins et al, 2018 ; Ramachandran et al, 2018 ). However, in contrast to the expectation of the crtS -to- ori2 copy control model, we observed that ori2 is active in the engineered strain VC73 in which the crtS lies downstream of ori2 analogous to the arrangement in NSCV2 (Figure 8 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…If the crtS site is replicated after ori2 has been copied by replication forks coming from ori1 as in the case of NSCV2, there is no need to initiate at ori2 because the copy number of crtS and ori2 are in balance already. The lack of initiation at ori2 in NSCV2 is therefore fully consistant with and confirmatory to the findings of the aforementioned studies ( de Lemos Martins et al, 2018 ; Ramachandran et al, 2018 ). However, in contrast to the expectation of the crtS -to- ori2 copy control model, we observed that ori2 is active in the engineered strain VC73 in which the crtS lies downstream of ori2 analogous to the arrangement in NSCV2 (Figure 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…These authors showed that it is the doubling of the crtS dosage rather than the process of replicating the crtS that triggers ori2 initiation which results in an even number of crtS and ori2 copies. This tendency of the regulatory system to produce similar copy numbers of crtS and ori2 have also been found in engineered systems with multiple crtS sites ( de Lemos Martins et al, 2018 ). If the crtS site is duplicated before ori2 as it is the case in two-chromosome V. cholerae strains, the ori2 copy number will be lower compared to crtS and consequently the initiation at ori2 will be triggered to restore crtS / ori2 copy number balance.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…a corresponding shift in triggering time of ori2 replication initiation with an increase in Chr2 size to coincide with termination and thus evolutionary conservation of this phenomenon (Kemter et al ., ). Additional interesting findings towards the understanding of the underlying mechanism are the binding of the ori2 initiator RctB as well as the protein Lrp to crtS and its spatial association with ori2 (Baek and Chattoraj, ; Val et al ., ; Ciaccia et al ., ) and the fact that crtS not only regulates the timing of Chr2 replication initiation but also controls Chr2 copy number (de Lemos Martins et al ., ; Ramachandran et al ., ).…”
Section: Exception To the Rule: Two Chromosome V Choleraementioning
confidence: 99%
“…Although how the context matters was not elaborated on, a new perspective on Chr2 replication was provided to explain the results. The idea is that the regulation of Chr2 replication is such that it maintains the parity of crtS to ori2 copy numbers (de Lemos Martins et al, 2018; Ramachandran et al, 2018). The crtS site normally resides in Chr1 and when the site number doubles upon passage of the Chr1 replication fork, Chr2 replication initiates and restores the crtS / ori2 ratio.…”
mentioning
confidence: 99%